2019
DOI: 10.1186/s43042-019-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of high level aminoglycoside resistance genes among clinical isolates of Enterococcus species

Abstract: Background: Enterococci are intrinsically resistant to clinically achievable concentrations of aminoglycosides. However, high-level resistance to aminoglycosides (HLAR) is primarily due to the acquisition of genes encoding aminoglycoside-modifying enzymes (AMEs). Aminoglycosides along with cell wall inhibitors are given clinically for treating enterococcal infections. The current study was conducted to investigate the rate of HLAR and to determine aminoglycoside resistance encoding genes profile in enterococca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Moreover, an almost similar prevalence rate of HLGR was reported in a study by Tian et al (2019) in china [44] . Diab et al (2019) [45] showed that 78% of isolates were HLGR, which is higher in comparison to this study result.…”
Section: Resultscontrasting
confidence: 78%
“…Moreover, an almost similar prevalence rate of HLGR was reported in a study by Tian et al (2019) in china [44] . Diab et al (2019) [45] showed that 78% of isolates were HLGR, which is higher in comparison to this study result.…”
Section: Resultscontrasting
confidence: 78%
“…The role of the APH(3’)-IIIa gene, as found in the DA70870 isolate, in providing resistance to aminoglycoside antibiotics such as kanamycin and streptomycin in S . aureus and Enterococci is well established [ 84 , 85 ]. Furthermore, among aminoglycoside-modifying enzymes, this particular type is less prevalent in S .…”
Section: Discussionmentioning
confidence: 99%
“…A moderate level of resistance was observed among high-level streptomycin in the present study. Although there is bactericidal activity among enterococci towards aminoglycosides, those antibiotics can be used together with cell wall inhibitors, such as ampicillin, for a synergistic effect, achieving a better outcome in the treatment of enterococcal infection [ 27 ]. Moreover, such combinations were considered in the treatment of infective endocarditis caused by E. faecalis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%